2023
DOI: 10.1177/0958305x231155494
|View full text |Cite
|
Sign up to set email alerts
|

The driving effect of digital economy on green transformation of manufacturing

Abstract: Under the double pressure of economic downturn and climate deterioration, the Chinese government needs to use the “double carbon” policy to drive the green transformation of the manufacturing industry. This article takes A-share manufacturing listed companies as the research object, constructs the enterprise digital economy investment index by text analysis and expert scoring method, and represents the degree of green transformation by enterprise green total factor productivity. At the theoretical level, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It also realizes real‐time monitoring, management, and accounting of industrial emissions, which enhances resource utilization efficiency (Zhou et al, 2021). Moreover, digital technology opens up the data resource channel for the interconnection and coordinated operation of the supply and demand sides of the industrial chain, realizing the double improvement of production efficiency and energy use efficiency and promoting Igt (Si et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also realizes real‐time monitoring, management, and accounting of industrial emissions, which enhances resource utilization efficiency (Zhou et al, 2021). Moreover, digital technology opens up the data resource channel for the interconnection and coordinated operation of the supply and demand sides of the industrial chain, realizing the double improvement of production efficiency and energy use efficiency and promoting Igt (Si et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the technology diffusion perspective of innovation theory, R&D personnel can communicate, deliberate, and generate innovative ideas on green technology anytime and anywhere by leveraging digital platforms, ultimately enhancing the speed and efficiency of innovation and fostering additional green technologies that promote Igt (Hao, Li, et al, 2023; Hao, Wang, et al, 2023). De, powered by big data technology, can accurately screen and identify green projects, industrial enterprises with substantial investments in green technology, and high‐energy‐consuming industrial enterprises (Si et al, 2023).…”
Section: Influence Mechanism and Research Hypothesismentioning
confidence: 99%
“…Some literature supports the view that digital transformation of enterprises has significant social significance, believing that it can significantly improve corporate social responsibility performance by strengthening internal control and weakening corporate opportunistic behavior (Hong Jun et al , 2021), enhance the strategic orientation of corporate social responsibility (Vollero et al , 2020) and narrow the labor income gap within enterprises. Digital transformation has enhanced corporate green innovation (He et al , 2023), promoted the green transformation of manufacturing enterprises and effectively improve enterprise environmental performance (Si et al , 2023). Xu et al (2023) confirmed the positive impact of enterprise digital transformation on the ecological environment based on the data of Chinese A-share resource-based-listed enterprises, and concluded that digitalization facilitates resource-based enterprises to break through the double constraints of resources and the environment, and significantly improves the environmental performance of the enterprises by accelerating the accumulation of human capital, stimulating the green technological innovation and enhancing the disclosure of environmental information and the ability of environmental governance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effects of digital technology on the economy are reflected not only in a single industry, but throughout the entire value chain [ 2 ], with significant implications for the entire economic system. The digital economy brings great innovation potential for enterprise development [ 3 ], and also promotes the exploitation of emerging green industries [ 4 ]. For example, the development of new energy, new materials, green environmental protection equipment and other fields make economic activities more efficient, intelligent and sustainable.…”
Section: Introductionmentioning
confidence: 99%